Potential of peer-to-peer bike sharing for relieving bike parking capacity shortage at train stations: an explorative analysis for the Netherlands - Goeverden, Kees van; Correia, Gonçalo (European Journal of Transport and Infrastructure Research, 2018)
In the Netherlands, many (mainly larger) train stations suffer from capacity shortages for bicycle parking as the result of a large increase in the use of the bicycle as a feeder mode. Sharing of parked bicycles with arriving train passengers who are in need of a bicycle for some time would decrease the number of parked bicycles and reduce the capacity shortage. The paper explores to which extent sharing of these bicycles relieves the capacity problem by investigating the maximum potential for reducing the peak of parked bicycles. This is the potential of the case when all considered participants (bicycle owners and those who are in need for a bicycle) are willing to share. The analyses are based on data of the Dutch National Travel Survey. The main result is that the potential is likely to be modest. The estimated maximum is for the large stations between 13% and 50%, the actual potential is likely to be significantly lower. The large range for the maximum can partly be explained by the uncertainty about the number of arriving train passengers that might shift to the bicycle for the last mile if sharing increases bicycle availability. A second result is that sharing can have a significant effect on the distribution of parked bicycles over the day. The current peak halfway the day can turn into a dip between two peaks in the traditional morning and evening peak hours.